The Role of Teachers In The Development of Moral Education In Primary Schools - Hadi, Rusnan; Ziyad, Muhammad Thoriq Bin; Nurhidayati, Nurhidayati; Sumardi, Lalu (Yayasan Cendekia Gagayunan Indonesia, 2025)
This study aims to analyze the role of teachers in the development of moral education in primary schools as a response to the increasing cases of moral degradation among students. Moral education serves as a fundamental foundation in shaping students' character, ethics, sense of responsibility, and social awareness from an early age. This research employs a literature review method using a qualitative descriptive approach by analyzing various relevant national and international journals. The findings indicate that teachers play a strategic role as role models, facilitators, and mentors in the process of internalizing moral values. The application of Albert Bandura’s social cognitive theory forms a crucial basis, emphasizing the importance of learning through observation, imitation, and reinforcement. Approaches such as moral discussions, role-playing, project-based learning, and the use of technology have proven effective in supporting students' character development. The success of moral education is influenced by teacher competence, behavioral consistency, family involvement, and support from the school and community environment. Therefore, strengthening teachers’ professional capacity through continuous training and multi-stakeholder collaboration becomes a key factor in nurturing morally grounded students in the modern era.